Desenvolvimento de um modelo de referência para linhas de manufatura de produtos modulares - Zambonato Junior, Renato (2015)
Achieving excellence in production is only possible when a product creation process receives the attention that enables integration between commercial reality and manufacturing capabilities of an industry. The energy required from the creative elaboration means a fundamental role in the success of the product. In the design phase of a product intended to be manufactured, there are many relationships between parts which form the final product, giving it the function and desired shape. This study proposes to explore this information, reorganizing, coding and grouping according to similar mounting characteristics. After data classification, crossing with information will be realized on the needs, capabilities or just demands of a factory in which it intends to introduce the assembly line under the studied product, making it possible to have clusters of pieces that may share the same devices and tools, labor and floor space, without losing focus on the ability end traits that each company will present. Also, it will be possible to view assembly lines options arising from the graphical analysis that will be performed and translated into easily interpreted images, accelerating the development process of assembly steps, reusing equipment.